Joint Attention in the Context of Hearing Loss: A Meta-Analysis and Narrative Synthesis. (29th September 2021) - Lammertink, Imme; Hermans, Daan; Stevens, Angela; van Bakel, Hedwig; Knoors, Harry; Vissers, Constance; Dirks, Evelien
Abstract: Joint attention is important for children's language development. We report two meta-analyses that demonstrate that the congruency in hearing status between parent and child affects the establishment and maintenance of joint attention. Dyads consisting of hearing parents and children with hearing loss, achieve fewer and briefer moments of joint attention in comparison to dyads of hearing parents and hearing children and dyads of deaf parents and deaf children. The theoretical and practical implications of these differences are discussed and placed in the context of two narrative syntheses. The first one focusing on parental strategies used to achieve and maintain moments of joint attention and the second one on the relation between joint attention and spoken language proficiency. We also expect that this review may serve as the start of quest towards a more detailed description (taxonomy) and operationalization of joint attention in the context of hearing loss.